Adaptation Strategies of Clove Farmers in Facing Climate Change in Taliabu Barat Sub-district Taliabu Island District North Maluku Province - Winda Pratiwi; Ilma Sarimustaqiyma Rianse; Muhammad Aswar Limi (International Journal of Technology and Education Research, 2025)
Climate change is one of the natural phenomena that has a considerable impact on agriculture. This study aims to find out (1) Clove Plant Productivity in Kramat Village, West Taliabu District, Taliabu Island Regency, North Maluku Province (2) Adaptation Strategies Carried out by Clove Farmers in Kramat Village, West Taliabu District, Taliabu Island Regency, North Maluku Province. The determination of the research location was carried out purely with the consideration that Kramat Village is one of the clove producers that has unstable climatic conditions and threatens the productivity of cloves which is the main source of livelihood for farmers. The number of clove farmer respondents was 36 farmers. The data analysis used was a descriptive-qualitative analysis with a Likert scale. The results of the study showed that the productivity of clove plants in Kramat Village, West Taliabu District, Taliabu Island Regency, was only 106.60 kg/ha/year. This low productivity is caused by climatic variations in high rainfall that occurred in Kramat Village, West Taliabu District with a range of 1811.9-5118.8 mm/year. The adaptation strategies carried out by clove farmers in the face of climate change that occurred in Kramat Village, West Taliabu District, Taliabu Island Regency, are the use of extension services, changes in planting time, the use of fertilizers, the selection of resistant varieties, the clearing of ground cover, the formation of farmer groups to share knowledge, business diversification, the use of more efficient irrigation technology, the application of agroforestry, and the adoption of crop insurance.